Improving Gross Motor Skills in Early Childhood Through Throwing and Catching Games Catch Football in Group B RA Darussalam NW Pungkang Academic Year 2024/2025 - Rukyah, Rukyah; Aini, Baiq Halimatuz Zuhrotul; Ismayadi, Ismayadi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study is entitled Improving Gross Motor Skills of Early Childhood Through Throwing and Catching Ball Games in Group B RA Darsussalam NW Pungkangng in the 2024/2025 Academic Year. This study aims to develop gross motor skills of children aged 5-6 years through throwing and catching ball games in group B RA Darsussalam NW Pungkangng. Formulate the research problem as follows: